(untitled) (Journal of Guidance and Counselling Studies, 2024)
This study explored the effect of rational emotive behaviour therapy on health risk-taking behaviour of in-school adolescents in Abia State. The study adopted a quasi-experimental design. Two research questions and one null hypothesis guided the study. The sample size of the study consisted of 32 in-school adolescents who were purposefully drawn from 778 senior secondary class II students with Health risk-taking behaviours in Abia State. The instrument used for data collection was a 30-item questionnaire titled Adolescents’ Health Risk-Taking Behaviour Identification Questionnaire (AHRTBIQ). The instrument was validated by three experts in order to establish its face validity. The reliability of the instrument was established using Pearson Moment Correlation Coefficient to establish the stability of the instrument which yielded a coefficient of 0.87; while Cronbach Alpha method was used to establish the internal consistency of the instrument, and the result indicated index values of 0.76. Data collected were analysed using mean and standard deviation to answer the research questions, and Analysis of Covariance (ANCOVA) to test the null hypothesis at 0.05 level of significance. The results among others showed that rational emotive behaviour therapy resulted to reduction of health risk-taking behaviour of in-school adolescents in Abia State at both the post-test and follow-up.